Labor market polarization over the business cycle - Christopher L. Foote; Richard W. Ryan (Federal Reserve Bank of Boston, 2014)
One of the most important long-run trends in the U.S. labor market is polarization, defined as the relative growth of employment in high-skill jobs (such as management and technical positions) and low-skill jobs (such as food-service and janitorial work) amid the concurrent decline in middle-skill jobs (such as clerical, construction, manufacturing, and retail occupations). Middle-skill job losses typically result from outsourcing labor to lower-wage countries or from substituting automated technologies for routine tasks. Economists are now beginning to study how long-run polarization might be related to short-run business cycles, but doing so requires the construction of quarterly datasets with consistent occupational data over long periods of time. The authors of this paper construct a new dataset of occupational employment and unemployment that extends from 1947:Q3 to 2013:Q4. Using this dataset, along with more-recent individual-level data from the Current Population Survey, the authors study how recessions typically affect employment in various occupations, what employment alternatives are available to middle-skill workers who become unemployed, and whether the ongoing erosion of middle-skill job opportunities is related to long-term declines in labor force participation among men.
Keywords: E24; J22; J23; J24; J62; J63; J64; 330